1985
DOI: 10.1073/pnas.82.3.849
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of the gene for the RNA-processing enzyme RNase III of Escherichia coli.

Abstract: A ColEl plasmid from the Clarke and Carbon collection [Clarke, L. & Carbon, J. (1976) CeU 9, 91-99] that contains a 14.4-kilobase Escherichia coli DNA insert complements the rnc-105 mutation, which destroys the activity of the RNA-processing enzyme RNase III. This insert and smaller restriction endonuclease fragments derived from it were cloned into the plasmid pBR329. A number of these recombinant plasmids complemented the rnc-lOS mutation in a recA genetic background. The smallest cloned fragment that comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
15
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 39 publications
2
15
0
Order By: Relevance
“…This possibility e out because none of the PAM or JFL strains 4 Table 1 are recA and they still show the era phe selection of recombinants with pNG187. The fin amount of RNase III (encoded by rnc) and Era present in wild-type E. coli K-12 is small compared with that of other proteins is in agreement with the conclusion that Era is a regulatory protein (3,8,15,22).…”
Section: Resultssupporting
confidence: 68%
“…This possibility e out because none of the PAM or JFL strains 4 Table 1 are recA and they still show the era phe selection of recombinants with pNG187. The fin amount of RNase III (encoded by rnc) and Era present in wild-type E. coli K-12 is small compared with that of other proteins is in agreement with the conclusion that Era is a regulatory protein (3,8,15,22).…”
Section: Resultssupporting
confidence: 68%
“…One distinct polypeptide band whose synthesis was directed by the mc+ insert of pBK13 was identified (lane 2). The apparent molecular mass of this polypeptide is 27 kDa, in close agreement with the reported 26-kDa molecular mass that was observed for RNase III (54 (Fig. 1A, lane 1) but not in the lane corresponding to the mutant strain (SK7621) (Fig.…”
Section: Resultssupporting
confidence: 76%
“…The plasmids used in this work are described in Table 2. Plasmid pBK2 was constructed by subcloning the 4.3-kbp EcoRI fragment containing mc from pLC7-47 (54) into the EcoRI site of pLG339 (43). Plasmid pBK12 was made by subcloning the 4.3-kbp EcoRI fragment containing mc from pLC7-47 into the EcoRI site of pBR325 (35).…”
mentioning
confidence: 99%
“…The rnc gene has been cloned previously, and the sequence of a -5-kilobase-pair (kbp) segment of DNA contiguous to rnc has been reported (1,37,38,43,55,58). Genetic studies reported here show that rnc, era, and recO form an operon.…”
mentioning
confidence: 99%